Fuentes para el estudio de la cultura mortuoria en los Andes: Reflexiones en torno a la obra Agonía, muerte y salvación en el norte del Virreinato peruano: 1780-1821 - Luza Pillco, Eduador (2021)
The historian Ruth Magali Rosas Navarro has published the result of her doctoral thesis in the monograph Agony, death and salvation in the north of the Peruvian Viceroyalty: 1780-1821 (Huelva: Universidad de Huelva, 2019). The work shows us in detail the concerns and preparations made when a person felt that his last hours were approaching. Facing illness, death and what came after were not solitary acts, but in the different processes the individual encountered specific characters and institutions that played a key role. Divided into three chapters, the annotated monograph focuses on the Piura region, north of the Peruvian coast, and covers the last fifty years of the colonial period, a stage in which the culture of death had its own characteristics.